KEBIJAKAN LUAR NEGERI IRAN MENYEPAKATI PERJANJIAN THE JOINT COMPREHENSIVE PLAN OF ACTION (JCPOA) DALAM PEMBATASAN PROGRAM NUKLIR IRAN 2013-2015 - Budianto, Karsan; ", M. Saeri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The purpose of the research "Iran's Foreign Policy In Agreeing The Joint Comprehensive Plan Of Action (JCPOA) Restricted Iran Nuclear Program 2013-2015" is to explain the causes of the formation of an agreement between Iran and the West (the US and its allies) related to the issue of Iran's nuclear development during this. This agreement has long been sought by the West against Iran in order to persuade Iran to willing to reduce and restrict the activities of the nuclear program he developed during this time. The development of nuclear technology by Iran during this turned out to have made its own concerns for Western nations will manufacture weapons of mass destruction carried out by Iran. Western effort to persuade Iran to forge a deal finally materialized after the expiration of the leadership of the Iranian president Ahmadinejad in 2013, and replaced by the new president of Iran, namely Hassan Rouhani.Borrowing the theory presented by James N. Rosenau in explaining the factors of a country taking its foreign policy, one of which is through the source Indiosinkratik (indiosyncratic sources) Through of this theory, the Iran policy in agreeing a collective agreement with Western countries because it is caused by the characteristics The new leadership style iran Hassan Rouhani.Key Word: The Joint Comprehensive Plan of Action, Iran, US, Idiosyncratic